Predictive model of the dropout intention of Chilean university students - López-Angulo, Yaranay; Sáez-Delgado, Fabiola; Mella-Norambuena, Javier; Bernardo, Ana B.; Díaz-Mujica, Alejandro (Frontiers in Psychology, 2023)
Dropping out of university studies is one of the current problems of Higher Education; the increased rates during the first year of the career is considerable around the world. Dropping out has negative social implications that are reflected at the personal, family, institutional, and educational levels. The aim of this study was to evaluate an explanatory model considering the mediation of university social satisfaction and perceived academic performance within the relationship perceived social support, social self-efficacy and academic purposes have with career satisfaction and dropout intention in chilean university students. A non-experimental explanatory design of latent and observed variables was used. Structural equation analyses with Mplus were performed. The sample consisted of 956 first year university students. The study complied with the ethical requirements for research with human subjects. As a result, an explanatory model with adequate adjustment indexes was obtained. When evaluating the explanatory capacity through the coefficient of determination (R2), it was observed that it explains 38.9% and 27.4% of the variance of the dropout intention and career satisfaction. This percentage of explanation indicates a large effect size in Social Sciences; therefore, they are considered optimal explanatory models. The mediation of university social satisfaction on the relationships of social support, social self-efficacy, and academic purposes with academic adjustment and dropout intention was respectively confirmed. The perception of academic performance has less influence on dropout intention and on satisfaction with the program among first-year students. The model obtained allows explaining the dropout intention and career satisfaction in first year students. In addition, it is composed of variables that can be modified in the interaction of students and professors.